Drying of industrial sludge waste in a conical spouted bed dryer. Effect of air temperature and air velocity. Issue 1 (2nd January 2019) - San José, M. J.; Alvarez, S.; López, R.
ABSTRACT: To determine the performance of a conical spouted bed dryer for the drying of sludge waste, an experimental study of drying in a spouted bed regime was performed under different experimental conditions. The drying performance was determined based on the time evolution of solid moisture content, and the influence of operating conditions (inlet air temperature, air flow rate, and bed mass) on the drying rate of sludge waste in spouted beds of a conical geometry was analyzed. GRAPHICAL ABSTRACT: